METHODS OF ANALYSIS OF FRAME STRUCTURES ACCORDING TO THE EUROCODE EN 1993-1-1 (Collection of scientific works «Modern structures of metal and wood», 2022)
In  accordance  with  the  guidelines  contained  in  the  European  standard prEN 1993-1-1 (draft September 2020), the stability of multi-storey frames should be checked taking into account the influence of geometric imperfections and deformation of the structure under the applied load. The article presents the calculation methods recommended by the European standard, which allow for the verification of frame bar stability. The calculation method was made dependent on  taking  into  account  the  influence  of  global  sway  imperfection  and  equivalent  local  bow imperfections,  as well as on the type of static  analysis used to determine the internal  forces and moments.